Book buddies [videorecording (DVD)] (PBS, 2024)
Inspire a love of reading and enjoy tales featuring favorite PBS KIDS bookworms. Daniel Tiger and O the Owl read together at the library. Then, Alma shares books with her community. Plus, Buster reads to win prizes, Watt and Windy visit the library, Rosie helps Mom set up for story time at the bookstore and much, much more.